Development of Islamic Religious Education Teaching Materials with a Meaning Model to Improve Elementary School Students' Creative Thinking Skills - Ummi, Zaitul (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Creative thinking skills are a must skill mastered by students at school. However, the fact is that this is not yet apparent learning process in class. One of the factors that influences .This can happen because the teaching materials used in class have not been used yet includes indicators of creative thinking skills. Therefore, it exists development of PAI teaching materials that can improve thinking skills student creativity is very necessary. This research aims to describe the development of teaching materials PAI is based on a meaning model to improve creative thinking skills students and responses.